MENGINTEGRASIKAN OLTRAD EGRANG DALAM PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN KESADARAN BUDAYA BAGI SISWA KELAS IV SDN 001 BARONG TONGKOK - Riska; Zulkarnaen (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop and implement a Project-Based Learning (PjBL) model in the teaching of Science and Social Studies (IPAS) for Grade IV students at elementary school, incorporating the theme of local wisdom through the traditional game egrang. The learning model is designed to increase students’ active participation, foster a love for local culture, and develop motor skills and teamwork through contextual and enjoyable activities. The research employs a Classroom Action Research (CAR) method conducted in three cycles at SD Negeri 001 Barong Tongkok, Kutai Barat Regency, involving 27 students (15 boys and 12 girls). The PJBL implementation followed six stages: (1) formulating essential questions, (2) collaboratively designing the project, (3) practicing the egrang game directly in the field, (4) monitoring and guiding students throughout the project, (5) evaluating the learning process and outcomes, and (6) presenting the project results through demonstrations. Learning resources included a Grade IV IPAS textbook and educational videos from YouTube projected using an LCD projector. Assessment was conducted both formatively and summatively. The results showed that implementing the PJBL model through direct practice was highly effective. Out of 27 students, 24 demonstrated significant improvement in motor skills, courage, and understanding of local culture. Although 3 students still required additional assistance in mastering basic egrang techniques, they showed positive progress throughout the learning process. In conclusion, the direct-practice-based PJBL model is highly suitable for IPAS learning with a local wisdom theme. It is recommended that egrang activities be integrated into national celebration events such as Independence Day (August 17th), Youth Pledge Day, or Cultural Day, to encourage ongoing student participation and support the preservation of traditional games as part of national cultural heritage.